Effects of bodybuilding on anxiety reduction: A literature review (Research, Society and Development, 2024)
Introduction: Anxiety is a natural response of the body to situations perceived as threatening, characterized by excessive fear and worry. The objective of this study was to analyze the scientific literature regarding the relationship between weight training and anxiety. Methodology: This is an integrative literature review, utilizing databases such as Medline, Lilacs, Scielo, and PubMed. Results: After filtering 362 articles, 21 were selected for the literature review, with a predominance of the English language. Discussion: Research indicates that resistance training benefits all age groups by improving self-confidence and self-control. Studies such as those by Shannon et al. (2023) suggest that greater frequency and intensity in weight training may provide protection against anxiety and depression. Conclusion: Weight training emerges as a valuable tool in combating the symptoms of anxiety and depression, offering not only physical benefits but also positive impacts on mental health.